EXPLORING THE ROLE OF PERCEIVED EXTERNAL CONTROL AND COMPUTER PLAYFULNESS IN MOBILE BANKING ADOPTION - Zaidie Chen; Fatihah Mohd; Nur Ain Ayunni Sabri, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This study examines the roles of Perceived External Control (PEC) and Computer Playfulness (CP) in shaping users' Behavioral Intention (BI) to adopt mobile banking, alongside Perceived Ease of Use (PEOU) within the Technology Acceptance Model (TAM) (Mathew, Sulphey, & Prabhakaran, 2014). PEC refers to users' beliefs about their ability to control the mobile banking environment, which can lead to increased confidence and BI (Marpaung, Dewi, Grace, Sudirman, & Sugiat, 2021). CP is characterized by enjoyment and engagement, positively influencing users' attitudes and BI (Salah & Ayyash, 2024). The study highlights the significance of PEC and CP in enhancing PEOU, which explains 65% of the variance in BI. PEC allows users to feel in command, reducing anxiety and enhancing user confidence (Gu, Lee, & Suh, 2009). CP contributes to a more enjoyable interaction, encouraging exploration and usage (Zhang, Lu, & Kizildag, 2018). PEOU acts as a crucial mediator between PEC, CP, and BI, indicating that users who find mobile banking easy to use are more likely to adopt it (Obaid, 2021). The research emphasizes the importance of enhancing PEOU to boost user adoption rates in mobile banking services (Aldammagh, Abdeljawad, & Obaid, 2021). However, factors such as trust and perceived risk also play critical roles in user acceptance, suggesting a multifaceted approach is necessary (Illia, Ngniatedema, & Huang, 2015; Obaid, 2021). By integrating playful elements and enhancing users' perceptions of external control, banks can improve PEOU and user satisfaction, aligning with the TAM and emphasizing the importance of perceived enjoyment and control in fostering user engagement.